2021
DOI: 10.3389/fncom.2021.646125
|View full text |Cite
|
Sign up to set email alerts
|

Spiking Neural Network (SNN) With Memristor Synapses Having Non-linear Weight Update

Abstract: Among many artificial neural networks, the research on Spike Neural Network (SNN), which mimics the energy-efficient signal system in the brain, is drawing much attention. Memristor is a promising candidate as a synaptic component for hardware implementation of SNN, but several non-ideal device properties are making it challengeable. In this work, we conducted an SNN simulation by adding a device model with a non-linear weight update to test the impact on SNN performance. We found that SNN has a strong toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 37 publications
0
30
0
1
Order By: Relevance
“…The main figure-of-merit of a memristor enabling its use as electronic synapse in a SNN is the spike-timing dependent plasticity (STDP) plot, a temporally asymmetric form of Hebbian learning that is induced by tight temporal correlations between the spikes of pre-and postsynaptic neurons 13 . A few implementations of SNN with memristors have been reported although a strong software perspective is employed in the studies in most of the cases 14,15 . Thereby both the synapses and neuron realisations have to be investigated deeply in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The main figure-of-merit of a memristor enabling its use as electronic synapse in a SNN is the spike-timing dependent plasticity (STDP) plot, a temporally asymmetric form of Hebbian learning that is induced by tight temporal correlations between the spikes of pre-and postsynaptic neurons 13 . A few implementations of SNN with memristors have been reported although a strong software perspective is employed in the studies in most of the cases 14,15 . Thereby both the synapses and neuron realisations have to be investigated deeply in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the update asymmetry of devices is more likely to affect the process of training neural networks (Kwon et al, 2020 ). Inspired by this motivation, they demonstrated that asymmetric non-linear devices are more powerful than symmetric linear devices (Brivio et al, 2018 , 2021 ; Kim et al, 2021 ). Our analytical tools and calibration method can be applied to illustrate the relationship between the update asymmetry of devices and its impact on training in detail.…”
Section: Impact Of Update Asymmetries On Neural Network Performancementioning
confidence: 99%
“…Different types of memristive devices are explored for their use in neuromorphic architectures. Among the most prominent ones are Phase Change Memory (PCM) (Boybat et al (2018a); Mehonic et al (2020)), Spin-Transfer Torque Magnetoresistive Random Access Memory (STT-MRAM) (Jung et al (2022); Ham et al (2021)) and Redox-based Random Access Memories (ReRAM) (Kim et al, 2021); Ziegler et al (2020); Bengel et al (2021a); Covi et al (2016); Park et al (2012)). For redox based resistive switches one can further differentiate between electrochemical metallization mechanism (ECM) cells and valence change mechanism (VCM) cells.…”
Section: Introductionmentioning
confidence: 99%